Terrorism and the Rise of Right-Wing Content in Israeli Books. (24th September 2018) - Mitts, Tamar
Abstract: In the past few years the Western world has witnessed a rise in the popularity of right-wing political discourse promoting nationalistic and exclusionary world views. While in many countries such rhetoric has surfaced in mainstream politics only recently, in Israel, right-wing ideology has been popular for almost two decades. Explanations for this phenomenon focus on Israeli citizens' attitudinal change in the face of exposure to terrorism but largely do not account for why such ideas remain popular over the long term, even after violence subsides. In this study I examine whether the long-lasting prominence of right-wing nationalistic politics in Israel is linked to the perpetuation of right-wing ideology in popular media. Analyzing the content of more than 70, 000 published books, I find that content related to the political right has increased in Israeli books after periods of terrorism, a change that has become more pronounced over the years.